Advances in Nanostructured Fluorescence Sensors for H2O2 Detection: Current Status and Future Direction - Hossein Pouri; Rakshya Panta; Prabhu Bharathan; Jiye Fang; Jin Zhang (Micro)
Hydrogen peroxide (H2O2) detection in both liquid and gas phases has garnered significant attention due to its importance in various biological and industrial processes. Monitoring H2O2 levels is essential for understanding its effects on biology, industry, and the environment. Significant advancements in the physical dimensions and performance of biosensors for H2O2 detection have been made, mainly through the integration of fluorescence techniques and nanotechnology. These advancements have resulted in more sensitive, selective, and versatile detection systems, enhancing our ability to monitor H2O2 in both liquid and gas phases effectively. However, limited comprehensive reviews exist on the detection of vaporized H2O2, which is used in disinfection and the production of explosive agents, making its detection vital. This review provides an overview of recent progress in nanostructured fluorescence sensors for H2O2 detection, covering both liquid and gas phases. It examines various fluorescence-based detection methods and focuses on emerging nanomaterials for sensor development. Additionally, it discusses the dual applications of H2O2 detection in biomedical and non-biomedical fields, offering insights into the current state of the field and future directions. Finally, the challenges and perspectives for developing novel nanostructured fluorescence sensors are presented to guide future research in this rapidly evolving area.